A GLP-1 analogue optimized for cAMP-biased signaling improves weight loss in obese mice - Jonathan D. Douros; Aaron Novikoff; Barent DuBois; Rebecca Rohlfs; Jacek Mokrosinski; Wouter F.J. Hogendorf; Robert Augustin; Myrte Merkestein; Lene Brandt Egaa Martini; Lars Linderoth; Elliot Gerrard; Janos Tibor Kodra; et al. (Molecular Metabolism)
Objective: Glucagon-like peptide 1 (GLP-1) receptor (GLP-1R) agonism is foundational to modern obesity pharmacotherapies. These compounds were engineered for maximal G protein alpha(s) (Gsα) signaling potency and downstream cAMP production. However, this strategy requires reconsideration as partial, biased GLP-1R agonists characterized by decreased Gsα signaling and disproportionate reductions in β-arrestin recruitment relative to the native ligand provide greater weight loss than full, balanced agonists in preclinical models. Methods: We tested the hypothesis that in vitro signaling bias, which considers both cAMP signaling and β-arrestin recruitment, better predicts weight loss efficacy in diet induced obese (DIO) rodents than cAMP potency alone. Results: Our data demonstrate that signaling bias significantly correlates to GLP-1R agonist mediated weight loss in diet-induced obese mice. We further characterized a protracted GLP-1 analogue (NNC5840) which exhibits a partial-Gsα, cAMP-biased GLP-1R signaling profile in vitro and demonstrates superior maximal body weight reduction compared to semaglutide in DIO mice. The NNC5840 weight loss profile is characterized by reduced in vivo potency but increased maximal efficacy. Conclusion: The data demonstrate that biased agonism is a strong predictor of in vivo efficacy for GLP-1R agonists independent of factors like intrinsic cAMP potency or pharmacokinetics. These data suggest that drug discovery screening strategies which take a holistic approach to target receptor signaling may provide more efficacious candidate molecules. The interpretations of these studies are limited by unknowns including how structural modifications to the biased GLP-1R agonist effect physiochemical properties of the molecules.